„Efectul școală” asupra performanțelor educaționale ale elevilor - Neagu, Gabriela (Calitatea Vieții, 2011)
This article presents the results of qualitative research: 16 focusgroups with teachers and parents from the Elementary School with classes I–VIII “Spiru Haret” from the Medgidia city (which is the beneficiary of a non-reimbursable financing through the project “A necessary support for the Roma and Turkish ethnicities from the Constanta County”) and from other seven schools in the cities: of Bacău, Buhuşi, Bucureşti, Medgidia and Piteşti. Within this project, an educational support program “school after school” was run in the first school. The analysis will focus on the evaluation of the factors that may influence the level of educational performances of the pupils, starting with the fact that the impact of an educational program might be enforced or, by the contrary, stopped through some caracteristics of the school: the relations among families and school, the relations among teachers, and their level of qualification, the atmosphere from the school and so on. The results of the analysis enhance the role of the school regarding the pupils’ educational performances.